Pendekatan Dakwah Al-Taṣfiyah wa Al-Tarbiyah Perspektif Shaikh Muḥammad Nāsiruddīn al-Albānī - Bimantara, Angger (STAI Ali bin Abi Thalib Surabaya, 2025)
This study aims to explain the daʿwah approach of al-tasfiyah wa al-tarbiyah according to Shaikh Muhammad Nāṣiruddīn al-Albānī and to assess its relevance in the context of daʿwah. The research employs a descriptive qualitative method using a library research approach. Primary sources were drawn from Shaikh al-Albānī’s works and analyzed through content analysis involving data reduction, presentation, and conclusion drawing. The findings reveal that al-taṣfiyah functions as the purification of Islamic teachings from doctrinal deviations, bidʿah practices, and traditions not rooted in the Qur’an and Sunnah, while al-tarbiyah serves as the education of Muslim generations with sound knowledge to be consistently practiced. Both aspects complement each other: al-taṣfiyah establishes the epistemological foundation, while al-tarbiyah ensures the continuity of daʿwah praxis. The novelty of this research lies in affirming that Shaikh al-Albānī’s thought offers an integrative daʿwah framework, not limited to purification or education alone but emphasizing their synthesis. The implication is that daʿwah strategies can be strengthened through an approach that balances purification and generational nurturing, making them more relevant in addressing globalization and the crisis of religious authority.